2000
DOI: 10.1191/0269215500cr372oa
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of a new pattern of electrical stimulation as a treatment for urinary stress incontinence: a randomized, double-blind, controlled trial

Abstract: Although promising, the improvement in pelvic floor function did not result in a reduction in symptoms in all patients. Further research is required to investigate the effects of the new stimulation in combination with pelvic floor exercises and to compare the new stimulation pattern with existing forms of electrical stimulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 29 publications
(21 reference statements)
1
16
0
1
Order By: Relevance
“…Other researchers found that electrical stimulation of no particular benefi t to women with stress UI because the symptom of urinary leaks did not decrease. 35 As expected, we found that women with predominantly stress UI did benefi t from exercise. However, those with the added electrical stimulation showed a greater small and unequally spread over the control and treatment groups, prohibiting the use of parametric tests.…”
Section: Research Reportsupporting
confidence: 79%
“…Other researchers found that electrical stimulation of no particular benefi t to women with stress UI because the symptom of urinary leaks did not decrease. 35 As expected, we found that women with predominantly stress UI did benefi t from exercise. However, those with the added electrical stimulation showed a greater small and unequally spread over the control and treatment groups, prohibiting the use of parametric tests.…”
Section: Research Reportsupporting
confidence: 79%
“…In contrast, another study 28 did not detect any statistically significant differences between electrical and sham electrical stimulation when pelvic floor muscle strength was measured using a device measuring vaginal squeeze pressure. However, if muscle strength was assessed using digital assessment, a statistical significant difference in favor of electrical stimulation was found.…”
Section: Discussionmentioning
confidence: 83%
“…Forty-seven (77.0%) papers used one of eight previously published incontinence-specific QOL measure (Table 2), of which the most commonly used were IIQ (reported in 19 papers), I-QoL (12 papers) and UDI (nine papers). The most frequently used combinations of incontinence-specific QOL measures were IIQ with UDI (eight papers [19][20][21][22][23][24][25][26]), and IIQ-7 with UDI-6 (five papers [25][26][27][28][29]). …”
Section: Stage 1: Review Of Measures Used In Clinical Trialsmentioning
confidence: 99%